2012
DOI: 10.1128/jcm.05386-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neisseria gonorrhoeae Multiple-Locus Variable-Number Tandem-Repeat Analysis, N. gonorrhoeae Multiantigen Sequence Typing, and Full-Length porB Gene Sequence Analysis for Molecular Epidemiological Typing

Abstract: The performance characteristics of Neisseria gonorrhoeae multilocus variable-number tandem-repeat analysis were evaluated, by comparison with N. gonorrhoeae multiantigen sequence typing and full-length porB sequence typing. Assessment of the relatedness of intra-and interpatient isolates showed that all three genotyping techniques display a high resolution and typeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…Concordance between MLVA and NG-MAST was very low in Indonesian strains, much lower than was reported in previous studies [ 26 , 27 ]. The number of studies comparing both MLVA and NG-MAST to type Ng strains is limited however, and the reported level of concordance between the two techniques varied greatly [ 26 28 ]. This could be caused by the different genetic regions of Ng targeted by these techniques [ 8 ].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Concordance between MLVA and NG-MAST was very low in Indonesian strains, much lower than was reported in previous studies [ 26 , 27 ]. The number of studies comparing both MLVA and NG-MAST to type Ng strains is limited however, and the reported level of concordance between the two techniques varied greatly [ 26 28 ]. This could be caused by the different genetic regions of Ng targeted by these techniques [ 8 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Mutations or genetic translocation in these regions probably occur independently [ 15 , 16 ]. In addition, discrepancy in the MLVA/NG-MAST concordance might relate to varying sample size and sample selection among studies [ 8 , 26 28 ]. Also this MLVA has been validated using mainly European strains; it could be that by addressing different targets for Indonesian strains, this concordance could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…It involves sequence-based typing using established PCR primers of two highly variable and polymorphic outer membrane protein genes, porB and tbpB by comparing the sequences to an open-access database (http://www.ng-mast.net/) (Martin et al , 2004). Although NG-MAST is the most frequently performed molecular typing method for N. gonorrhoeae , it requires multiple PCR amplification and sequencing reactions, making it more laborious than other typing methods (Heymans et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This typing scheme was first evaluated for N. gonorrhoeae in 2012 (90). Multilocus variable-number tandem-repeat analysis (MLVA) is a technique that involves amplifying variable-number tandem-repeats using PCR, followed by size determination which is typically done through capillary electrophoresis.…”
Section: Multilocus Variable-number Tandem Repeat Analysismentioning
confidence: 99%
“…Based on the four studies that utilised this method for assessing N. gonorrhoeae populations, MLVA's high discriminatory power allows it to remain as a competitive typing tool for microepidemiological investigations (93). Due to the highly polymorphic nature of MLVA, it is now commonly recognised that single locus variants are considered indistinguishable so that clusters are retained at an appropriate level (90,93,94). However, the technique does lack defined regions for VNTR (84), which leads to a lack of reproducibility.…”
Section: Multilocus Variable-number Tandem Repeat Analysismentioning
confidence: 99%